Argentina : Ex-Post Evaluation of Exceptional Access Under the 2018 Stand-By Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2021)
On June 20, 2018, the Executive Board approved the largest stand-by arrangement in the Fund's history, in support of Argentina's 2018-21 economic program. After an augmentation in October 2018, access under the arrangement amounted to USD 57 billion (1,227 percent of Argentina's IMF quota). The program saw only four of the planned twelve reviews completed, and did not fulfil the objectives of restoring confidence in fiscal and external viability while fostering economic growth. The arrangement was canceled on July 24, 2020.